Study Of Pineapple Exocarp, Gadung Tuber And Liquid Of Pulp Cocoa Fermentation As Latex Coagulants Toward Rubber Quality - Ayu Valentina; Yohanes Hendro Agus; Maria Marina Herawati (Agric, 2020)
Some rubber farmers in Indonesia use un-recommended latex coagulant and it causes bad quality of rubber. The utilization of organic latex coagulants has the potential way to improve rubber quality. The aim of this study was to determine the effect of pineapple exocarp extract, gadung tuber extract and liquid of pulp cocoa fermentation as latex coagulants toward rubber quality. The study was using Randomized Completely Block Design with six treatments and four replications the treatments tested was 10 ml and 20 ml pineapple exocarp extract, 10 ml and 20 ml gadung extract and 10 ml and 20 ml liquid of pulp cocoa fermentation. The parameters observed were contact time, weight of rubber and rubber characteristic which are comprised of serum clarity, rubber color and rubber stinky smell produced, ash content and volatile matter compared to Standart Indonesian Rubber (SIR) 20. The result of this study showed that 20 ml latex coagulant had faster contact time than others and increased weight of the rubber. It showed that rubbers produced a bit stinky smell as well, it was better than rubbers produced by inorganic latex coagulant.